Chronology of a sedimentary sequence from the land–ocean interaction zone in the North Jiangsu Basin. (10th April 2021) - Shu, Qiang; Zhao, Yifei; Frechen, Manfred; Zhang, Jingran; Chen, Ye; Liu, Yu; Yang, Peipei
Abstract: The North Jiangsu Basin (NJB), located in the western part of the North Jiangsu-South Yellow Sea Basin, is a critical region providing invaluable archives about the evolution processes of the land-ocean interchange and climatic environments in a coastal zone. Chronology is of crucial importance to reconstruct the timing of sea-level eustacy, and shoreline changes, as well as the evolution of the regional environment by means of numerical dating to determine the age of sedimentary strata in the sea–land interaction zone of the NJB. However, sediment dating in the NJB remains controversial due to limitations in the quantity and quality of chronological data. Therefore, the sediments in the Jianhu Gangxi (GX) profile of the NJB were analyzed in this study by applying both fine-grained quartz optically stimulated luminescence (OSL) dating and 14 C dating. The results were used to discuss the processes of regional environment evolution. The OSL dating of fine-grained quartz components in sediments was found to be a reliable method to determine deposition ages of sediments in the land-sea interaction zone in the NJB. The combination of OSL and accelerator mass spectrometry 14 C dating techniques allowed a reliable and high-resolution chronological framework for the GX profile. Since the last glaciation, the sedimentary environment in the eastern portion of the NJB changed significantly. In particular: (1) between 13 and 7.25 ka B.P, the area of interest was dominated by lacustrine deposition within a stable sedimentary environment with low deposition rates; (2) from 7.25 to 6.45 ka B.P, marine transgression events occurred, and the deposition rate increased rapidly in an area of land-sea interaction; (3) after 6.45 ka B.P, a regression event occurred, and the study area transformed into a lowland lake environment.